Melatonin protects inner ear against radiation damage in rats. (21st May 2015) - Karaer, Isil; Simsek, Gokce; Gul, Mehmet; Bahar, Leyla; Gürocak, Simay; Parlakpinar, Hakan; Nuransoy, Ayse
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To examine the effects of N‐acetyl‐5‐methoxytryptamine (melatonin) on radiation‐induced inner ear damage. Study Design An experimental animal model. Methods Forty rats were randomized into five groups, as follows: 1) melatonin and then radiotherapy group (n = 8), which received intraperitoneal (i.p.) melatonin (5 mg/kg) followed by irradiation 30 minutes later; 2) radiotherapy and then melatonin group (n = 8), which received irradiation with i.p. melatonin (5 mg/kg) 30 minutes later; 3) melatonin group (n = 8), which received i.p. melatonin (5 mg/kg); 4) radiotherapy group (n = 8), which underwent only irradiation; 5) and the control group (n = 8), which received i.p. 0.9% NaCl. The medications and irradiation were administered for 5 days. All rats underwent the distortion product otoacoustic emission (DPOAE) test before and 10 days after the experiment. The middle ears of the rats were excised, and assessment of tissue alterations in the organs of Corti, spiral ganglions, and stria vascularis were compared among the groups. Results In the radiotherapy group, the DPOAE amplitudes at frequencies of 4000 to 6000 Hz were significantly decreased when compared with the controls. The DPOAE amplitudes both in the melatonin and then radiotherapy group and the radiotherapy and then melatonin group exhibited better values than they did in the radiotherapy group. Histopathological evidence of damage to the organs of Corti, spiral ganglions, and stria vascularis damage was markedly reduced in both these two groups when compared to the radiotherapy group. Conclusion These results indicate that melatonin may have significant ameliorative effects on cochlear damage secondary to ionizing radiation. Laryngoscope, 125:E345–E349, 2015